Pengembangan Media Pembelajaran Mobile Learning berbasis Problem Solving untuk Meningkatkan Hasil Belajar IPAS - Luthfi Tsaniyyati; Aldina Eka Andriani (Postgraduate, University of Mataram, 2024)
Teachers have not optimally used technology learning media and have not implemented problem solving learning models, causing low student learning outcomes. The research objective is to develop, test feasibility, and measure effectiveness of Mobile Learning based on Problem Solving to improve IPAS learning outcomes for class V. This type of research is Research and Development with the Borg & Gall model. The research subjects were 21 class V students at SDN 02 Jatipurwo Karanganyar. Data collection techniques use tests (pretest, posttest) and non-tests (observation, interviews, questionnaires). Data analysis was carried out using normality test techniques, t test, and N-Gain test. The research results show: Mobile Learning based on Problem Solving was developed using the canva application containing a cover, learning outcomes, instructions for use, developer profile, references, accompanied by learning objectives, concept maps, materials and evaluation questions; the feasible of the media is shown from the validity test of material experts, media experts, teachers and students who receive a very feasible category; and effectiveness is shown from the analysis of pretest and posttest scores. The t test results get a sig value. (2-tailed) 0.000 < 0.005. The N-Gain test result is 0.4234 in the medium category. The conclusions in this research show that the development of Mobile Learning based on Problem Solving has been successfully developed, is very feasible, and is effectively used to improve the science and science learning outcomes of class V students at SDN 02 Jatipurwo Karanganyar